Incorporation of in Natura and Calcined Red Muds into Clay Ceramic - Larissa da Silva Ribeiro; Michelle Pereira Babisk; Ulisses Soares do Prado; Sergio Neves Monteiro; Carlos Mauricio Fontes Vieira (Materials Research, 2015)
Brazil is one of the world greatest aluminum producer and also comprises a large industrial sector dedicated to the production of alumina (Al2O3) by the traditional Bayer process. During this process an insoluble residue, known as red-mud, is generated and normally discarded. A possible use for the red mud is its incorporation into clay ceramics. Indeed, this has been a solution not only for the red mud but also for residues of different industrial segments. The common clay, like the kaolinite, versatility allows the incorporation of several types of residues. The red mud, in addition to compounds like silica and alumina that are compatible with clays, is also composed of iron, sodium, calcium and other elements that confer important characteristics to ceramic products. Thus, the present work investigated the incorporation of up 60 wt% of distinct red muds, one as processed, in natura, and the other calcined at 900 °C, into clay ceramics. Both red muds act as inert materials without improving the pure clay ceramic properties.